Skin color and tissue thickness effects on transmittance, reflectance, and skin temperature when using 635 and 808 nm lasers in low intensity therapeutics. Issue 4 (27th November 2017) - Souza‐Barros, Leanna; Dhaidan, Ghaith; Maunula, Mikko; Solomon, Vaeda; Gabison, Sharon; Lilge, Lothar; Nussbaum, Ethne L.
Abstract : Objective: To examine the role of skin color and tissue thickness on transmittance, reflectance, and skin heating using red and infrared laser light. Methods: Forty volunteers were measured for skin color and skin‐fold thickness at a standardized site near the elbow. Transmittance, reflectance and skin temperature were recorded for energy doses of 2, 6, 9, and 12 Joules using 635 nm (36 mW) and 808 nm (40 mW) wavelength laser diodes with irradiances within American National Standards Institute safety guidelines (4.88 mm diameter, 0.192 W/cm 2 and 4.88 mm diameter, 0.214 W/cm 2, respectively). Results: The key factors affecting reflectance to an important degree were skin color and wavelength. However, the skin color effects were different for the two wavelengths: reflectance decreased for darker skin with a greater decrease for red light than near infrared light. Transmittance was greater using 808 nm compared with 635 nm. However, the effect was partly lost when the skin was dark rather than light, and was increasingly lost as tissue thickness increased. Dose had an increasing effect on temperature (0.7–1.6°C across the 6, 9, and 12 J doses); any effects of wavelength, skin color, and tissue thickness were insignificant compared to dose effects. Subjects themselves were not aware of the increased skin temperature. Transmittance and reflectance changes as a function of energy were very small and likely of no clinical significance. Absorption did not change with higher energy doses and increasing temperature. Conclusion: Skin color and skin thickness affect transmittance and reflectance of laser light and must be accounted for when selecting energy dose to ensure therapeutic effectiveness at the target tissue. Skin heating appears not to be a concern when using 635 and 808 nm lasers at energy doses of up to 12 J and irradiance within American National Standards Institute standards. Photobiomodulation therapy should never exceed the American National Standards Institute recommendation for the maximum permissible exposure to the skin. Lasers Surg. Med. 50:291–301, 2018. © 2017 Wiley Periodicals, Inc.